Avaliação da suplementação de farelo de soja com diferentes valores de proteína não degradada no rúmen (PNDR) para cordeiros mantidos a pasto em período de estiagem - Vieira, João Acácio (Universidade Federal de São Carlos, 2022)
The experimental test was carried out at the sheep center of the Federal University of São Carlos - Lagoa do Sino campus, where 10 Santa Inês lambs were submitted, being males and females different allocated in two treatments based on protein supplementation (T1 corresponding to 16 % and T2 at 20% protein) in the animals' diet, with 5 repetitions each, composing a completely randomized design. Parameters such as weight gain (WG), daily feed intake (CR), feed conversion (CAS) to be evaluated. Data were always collected by the same evaluator, in addition to data collection on serum levels to be analyzed in the laboratory, such as albumin content and urea-N concentration. The present study aimed to evaluate different levels of protein in the diet of Santa Inês lambs during the dry season. For GP, CR and CAS the two diets (treatments) were equivalent according to the statistical analyses. However, albumin content and urea-N concentration showed differences between treatments T1 and T2.
Evaluation of soybean meal supplementation with different values of rumen undegradable protein (RUP) for lambs kept on pasture in the dry season
Keywords: Ovinocultura; Suplementação; Ruminantes; CIENCIAS AGRARIAS::ZOOTECNIA::NUTRICAO E ALIMENTACAO ANIMAL; CIENCIAS AGRARIAS::ZOOTECNIA::PASTAGEM E FORRAGICULTURA